The Complexity of Verification and Validation Testing in Component Based Software Engineering - Malla Reddy, Jogannagari; Parashu Ramulu, Kothuri (International Journal of Computer Sciences and Engineering, 2025)
There is a huge need of software professional to develop the better quality systems in rapid time to satisfy the customer needs. The component based technologies fulfil the achievement to make this possible. The modern systems have practically too complex behaviour. The complex systems developed with reusable components has many features such as lower costs and shortened development lifecycles. The component software development places the significant challenges like system integration and testing to build the software products. The verification and validation techniques are essential to ensure the software quality for component based producers. Accomplishing these techniques in the reusable component building is not a simple task. This paper focuses the various difficulties of these testing in various stages of component based software engineering.